(untitled) (Revista Espaço e Geografia, 2022)
The implementation and the development of the Gleba Celeste, in the Central-North of Mato Grosso, constitute a symbol of the recent occupation of the Amazônia south border. The growth of the Sinop city and neighbors county like Vera, Cláudia and Santa Carmem, testifies the expansion vitality of the pioneering front in this region. The Landsat satellite images allow to visualize and to schematize the expansion phases that lead to a new areas the growth of increasing deforestation practices characterizing the urban center stage.